Parameter identification of Yoshida-Uemori combined hardening model by using a variable step size firefly algorithm - Sener, Bora (WALTER DE GRUYTER GMBH, 2024)
The material behavior under cyclic loading is more complex than under monotonic loading and the usage of the sophisticated constitutive models is required to accurately define the elastoplastic behaviors of the advanced high-strength steels and aluminum alloys. These models involve the numerous material parameters that are determined from cyclic tests and accurate calibration of the variables has a great influence on the description of the material response. Therefore, the development of a precise and robust identification method is needed to obtain reliable results. In this study, a systematic methodology depending upon the firefly algorithm (FA) with variable step size has been developed and Yoshida-Uemori combined hardening model parameters of a dual-phase steel (DP980) and an aluminum alloy (AA6XXX-T4) are determined. The identified parameters are verified based on comparisons between the finite element simulations of the cyclic uniaxial tension-compression tests and experimental data and also the search performance of the variable FA is evaluated by comparing it with the standard FA. It is seen from these comparisons that variable FA can easily find and rapidly converge to the global optimum solutions.
Keywords: Yoshida-Uemori hardening model; finite element simulation; cyclic loading; firefly algorithm; step size; STRAIN CYCLIC PLASTICITY; KRIGING SURROGATE MODEL; DESIGN; CRASHWORTHINESS; OPTIMIZATION; Materials Science